Low-dose gemcitabine depletes regulatory T cells and improves survival in the orthotopic Panc02 model of pancreatic cancer - Shevchenko, Ivan; Karakhanova, Svetlana; Soltek, Sabine; Link, Julia; Bayry, Jagadeesh; Werner, Jens; Umansky, Viktor; Bazhin, Alexandr V. (International journal of cancer, 2013)
What's new? Regulatory T cells (Treg) appear to contribute to poor prognosis in patients with pancreatic ductal adenocarcinoma (PDAC), suggesting that Treg cells are key therapeutic targets.
First published: 12 December 2012
Gesehen am 26.01.2022